PEMODELAN PERSAMAAN ARRHENIUS UNTUK MEMPREDIKSI UMUR SIMPAN PENYEDAP RASA CANGKANG RAJUNGAN - Nurhidajah Nurhidajah; Boby Pranata; Diode Yonata (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
The aim of this research is to determine the shelf life of seasoning of swimming crab shell in metalized packaging, which is stored at various temperatures using the Arrhenius modeling. Seasoning are packaged using metalized packaging with a thickness of 0.06 mm, which is stored at 25ºC, 35ºC, and 45ºC for 8 weeks with 75% humudity. The parameters used for measuring shelf life are initial moisture content, critical water, and changes in water content during storage. In addition, analysis of hygroscopicity and water activities (aw) value of seasoning as supporting parameters were also carried out. The results showed that seasoning that the seasoning of the swimming crab shells was classified as a hygroscopic product, had moisture content, and aw values a low during storage. The longest shelf life of the swimming crab shell seasoning is storage at 25ºC, reaching 62 weeks based on moisture content parameters.